Evaluasi Program Pembelajaran IPS di Sekolah Dasar Negeri 126 Lagoe - Herwin Herwin (Program Studi PGSD, Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2019)
This study aims to describe the quality of learning and social studies learning output at SDN 126 Lagoe, Lilirilau District, Soppeng Regency. This study is an evaluative study using the EKOP evaluation model. Data collection used to obtain information in the quality domain is used by the questionnaire method. In the realm of technical output used in addition to the questionnaire is also a documentation technique. The data analysis technique used in this study was a descriptive quantitative analysis technique. The results showed that the quality of social studies learning was in good qualifications. The learning process in social studies learning is organized well. Social studies learning output is in good qualifications. Learning outcomes obtained after the Social Studies learning process took place were in the good category.